HASIL TUMPANG SARI JAGUNG (Zea mays L.) DAN KACANG MERAH (Phaseolus vulgaris L.) PADA JARAK TANAM JAGUNG YANG BERBEDA - Maria Klara Salli (Politeknik Pertanian Negeri Kupang, 2008)
Intercropping means planting one plant or more together or simultaneously at the same land every year. This system reduces failure risks due to drought, pest and disease. It also optimizes production at narrower land to help farmers dealing with food decline. Together with many legumes, any crops in this system maintain soil nutrient by providing nitrogen fixation, suppressing weed growth, and improving the nutrient given from different production of crops.The experiment was designed with split plot design in Randomized Block Design. Main plot design is corn planting space consisted of common bean belt with two levels i.e. single row and two rows.The results shown that the intercropping system gave the disparities in yields and also there are two planting system which provides highest yields i.e. 80 x 20 cm planting space with separated single row of common bean (9,02 ton ha-1 and 7,80 ton ha-1) and 100 x 20 cm planting space which interacted with two rows of common bean (1,49 ton ha-1).Keywords: difference planting, corn, red bean, intercropping.